Some Basic Properties of Completely Prime Ideals in Near Rings - Pairote Yiarayong (Journal of Mathematical and Fundamental Sciences, 2015)
In this investigation we studied completely prime, weakly completely prime, quasi completely prime and weakly quasi completely prime ideals in near-rings. Some characterizations of completely prime and weakly completely prime ideals were obtained. Moreover, we investigated relationships between completely prime and weakly completely prime ideals in near-rings. Finally, we obtained necessary and sufficient conditions for a weakly completely prime ideal to be a completely prime ideal.